2019
DOI: 10.1021/acschemneuro.9b00375
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bromine-Containing Paroxetine Analogue Provides Mechanistic Clues for Binding Ambiguity at the Central Primary Binding Site of the Serotonin Transporter

Abstract: The serotonin transporter (SERT) is the primary target for the selective serotonin reuptake inhibitors (SSRIs). However, the structural basis for the extraordinarily high binding affinity of the widely prescribed SSRI, paroxetine, to human SERT (hSERT) has not yet been fully elucidated. Our previous findings unveiled a plausible ambiguity in paroxetine's binding orientations that may constitute an integral component of this SSRI's high affinity for hSERT. Herein, we investigate factors contributing to paroxet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 32 publications
1
20
0
1
Order By: Relevance
“…1b,c) also reduced paroxetine inhibition and binding, likely also disrupting these interactions. Although the effects were less severe when compared to paroxetine, Br-paroxetine binding and inhibition was also reduced for Ala169Asp 20 . Thus, these mutations highlight the importance of subsite B interactions in paroxetine binding but they cannot be used to demonstrate the inhibitor pose because, in the ABC or ACB poses, either the dioxol or fluorine of paroxetine could act as a hydrogen-bond acceptor in subsite B.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…1b,c) also reduced paroxetine inhibition and binding, likely also disrupting these interactions. Although the effects were less severe when compared to paroxetine, Br-paroxetine binding and inhibition was also reduced for Ala169Asp 20 . Thus, these mutations highlight the importance of subsite B interactions in paroxetine binding but they cannot be used to demonstrate the inhibitor pose because, in the ABC or ACB poses, either the dioxol or fluorine of paroxetine could act as a hydrogen-bond acceptor in subsite B.…”
Section: Discussionmentioning
confidence: 92%
“…The binding of paroxetine to SERT has been extensively debated 8,9,[18][19][20] . The first x-ray structure of the ts3-SERT variant demonstrated that the binding pose is such that the piperidine, benzodioxol, and fluorophenyl groups occupy subsites A, B, and C respectively, in the ABC pose 9 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, common methods for (-)-paroxetine synthesis can require the aromatic substituent to be introduced before stereoselective steps or ring construction, reducing flexibility of the process 20,[28][29][30][31][32][33][34] . Nevertheless, during the preparation of this work, the synthesis of Br-paroxetine was reported using an asymmetric conjugate addition and its binding to SERT has been extensively studied 20,30 .…”
Section: Resultsmentioning
confidence: 99%